Consequences of Rural-to-Urban Migration in Ladakh: A Comprehensive Analysis of Impacts on Areas of Origin and Destination (International Journal of Food and Nutritional Sciences, 2022)
This research paper investigates the growing trend of rural-to-urban migration in Ladakh, motivated by global pursuits for enhanced opportunities and living standards. Despite its growing significance, the migration phenomenon in Ladakh remains insufficiently examined, lacking reliable data. The study delves into the multifaceted impacts of this migration on both the areas of origin and destination. Detrimental consequences at the origin involve depopulation, abandonment of traditional occupations, disruption of social ties, and the feminization of agriculture. Conversely, positive outcomes include increased income and remittances. Destination areas experience urbanization, heightened population density, housing challenges, the emergence of private education institutions, and environmental pollution as repercussions of migration. Addressing these intricate, context-dependent socioeconomic and environmental implications necessitates a comprehensive understanding, urging policymakers, urban planners, and stakeholders to take informed actions.